Evaluation Apache Scoring System For An Indicator of Mortality Rate in ICUPatients : A Systematic Review - Ayu Risky Susanti Putri; Tintin Sukartini; Laily Hidayati (Universitas Pahlawan Tuanku Tambusai, 2026)
AbstractBackground: APACHE II is used to screen for mortality risk in critically ill patients. Where critical conditionswith different diagnoses result in different mortality risk levels. Methods: This study used a systematic reviewdesign. The articles selected for this study were published between 2020 and 2025, and the search wasconducted using four databases: Scopus, PubMed, EBSCO, and ProQuest. The research followed thePreferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Results: Sevenarticles met the inclusion criteria after being evaluated for quality using the JBI Critical Appraisal Tool todetermine their suitability for systematic review. Conclusion: This study shows that early detection usingAPACHEII will improve patient outcomes.Keywords: APACHE II, Critical ill patient, Mortalitas